F Tests with Random Sample Sizes - Nunes, Célia (2020)
Submitted by FERREIRA (dario@ubi.pt) on 2020-02-05T22:37:31Z No. of bitstreams: 1 2010 - F tests with random sample sizes.pdf: 94566 bytes, checksum: beb753885546f3f5357cb74272b27099 (MD5)